Platimun Compounds Involving New Anti-cancer Mechanism - Odani, Akira (Biomedical Research on Trace Elements, 2011)
Cisplatin, clinically used anticancer Pt(II) complex, has been believed to attack DNA to form Pt-N7(Guanine) coordination, and Pt-G bond is protected from DNA repair enzyme by the aromatic ring stacking between Pt-G and Phe side chain in Pt-DNA-HMG protein adduct. The adduct mimicked 4N coordinated Pt(II) complexes M(DA)(AtCn) involving with metal coordinated aromatic diamine (DA) and anthracene ring side chain in AtCn, which could not coordinate DNA, showed not only in vitro cytotoxicity for human cancer cell lines but also strong inhibition with protein interaction such as the proteasome. The bio-activity indicated the structural dependence of both DA and AtCn. This should relate with the intramolecular aromatic ring stacking interaction which was evidenced by the X-ray structure in crystal and the H-1 NMR in H2O solution. Importantly the Pt(II) complexes showed similar bioactivity in cisplatin resistance cancer cell. These experimental results showed that the Pt complexes involving stacking structure might be new type anticancer metal compounds.